Transcriptomic Analysis of Fusarium oxysporum Stress-Induced Pathosystem and Screening of Fom-2 Interaction Factors in Contrasted Melon Plants - Yang, Tiantian; Liu, Jiajun; Li, Xiaomei; Amanullah, Sikandar; Lu, Xueyan; Zhang, Mingchong; Zhang, Yanhang; Luan, Feishi; Liu, Hongyu; Wang, Xuezheng (Frontiers in Plant Science, 2022)
Melon wilt is an important worldwide disease which is mainly triggered by Fusarium oxysporum (f. sp. melonis race 1). Herein, transcriptome sequencing and Yeast two-hybrid (Y2H) methods were used for analysing the candidate differentially expressed genes (DEGs) regulating the mechanisms of Fusarium oxysporum induced stress in contrasted melon (M4-45 "susceptible" and MR-1 "resistant"). The interaction factors of Fom-2 resistance genes were also studied to investigate the mechanism towards the pathosystem. Transcriptomic analysis exhibited total 129.99 Gb sequence reads, 1,904 new genes; however, identified DEGs analysis revealed total 144 specific genes (50 up-regulated & 94 down-regulated) for M4-45 material and 104 specific genes (71 up-regulated & 33 down-regulated) were categorized for MR-1 material. The analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway depicted candidate genes, including phenylalanine metabolism/phenylpropane biosynthesis, plants-pathogen interaction, and signal transduction of plant hormones, that were mainly involved in the metabolic pathways of disease resistance. The weighted gene co-expression network analysis (WGCNA) analysis revealed the strong correlation module and similarly identified that genes linked with disease resistance encode course proteins, transcription factors, protein kinase, benzene propane biosynthesis path, plant-pathogen interaction path, and glutathione S transferase. Meanwhile, the resistance-related DEGs expression in MR-1 was relatively abundant as compare to M4-45, and cell wall associated receptor kinases (MELO3C008452 and MELO3C008453), heat shock protein (Cucumis_melo_newGene_172), defensin-like protein (Cucumis_melo_newGene_5490) and disease resistance response protein (MELO3C016325), activator response protein (MELO3C021623), leucine-rich repeat receptor protein kinase (MELO3C024412), lactyl glutathione ligase (Cucumis_melo_newGene_36), and unknown protein (MELO3C007588) were persisted by exhibiting the up-regulated expressions. At transcription level, the interaction factors between candidate genes of Fusarium oxysporum induced stress and Y2H screening signified the involvement of MYB transcription factors (MELO3C009678 and MELO3C014597), BZIP (MELO3C011839 and MELO3C019349), unknown proteins, and key enzymes in the ubiquitination process (4XM334FK014). These candidate genes were further verified within infected melon plants of Fusarium oxysporum (race 1), exogenously treated with Abscisic acid (ABA), Methyl Jasmonite (MeJA), and Salicylic acid (SA), using fluorescence quantitative polymerase chain reaction (qRT-PCR) analysis. The obtained results signified that SA signaling pathway is effectively regulating the Fom-2 gene activity.